COMPLETE TEXT EDITING.SCHIRIFT'S PLACE IN PHOTSHOP 7. USING 5 AMAL TUPE EQUIPMENT OVER THE TEXT - Noriboeva Dilnozaxon Tursunboy qizi (Western European Studies, 2024)
This article explores advanced techniques in digital image processing, focusing on forming and editing contours, the concept of forming masks, and methods for lowering the effect of filters. The paper provides a comprehensive overview, including an introduction to the key concepts, a review of existing literature, detailed methodologies, results, discussion, conclusions, and suggestions for future research.
Keywords: Digital image processing; contour editing; mask formation